Новый вид рода ортоспланхнус - Orthosplanchnus pygmaeus (Trematoda, Campulidae) - паразит кита - Юрахно, М.В. (Вестник зоологии, 1967)
A new trematode Orthosplanchnus pygmaeus sp. n., obtained from the grey whale (Eschrichtius gibbosus) of the Chukotsk Sea, is described. The new species differs from the known ones of the genus Orthosplanchnus in the smaller dimensions of the body and various organs, in the disposition of the yolk glands and the absence of the cirrus thorns.